Pengaruh Penggunaan Media Nearpod Terhadap Kemampuan Numerasi - Zusgi, Bihabdila Aira Putri; Hadi, Windia (MATH-EDU: Jurnal Ilmu Pendidikan Matematika, 2024)
This research aims to determine the effect of using nearpod media on numeracy abilities. This research uses a quasi-quantitative experimental method with a posttest-only control design. Subjects were taken using a purposive sampling technique with a total sample of 64. The instrument used was 5 questions which had been tested for validity and reliability and had been declared valid and reliable in the high category. Furthermore, the results of data analysis were carried out using SPSS 27. The test results using Kolmogorov Smirnov were declared normal with a value of 0.20 and the Levene statistics results were declared homogeneous with a value of 0.81. Then hypothesis testing was carried out and obtained significant results that there was an influence between the use of nearpod media and numeracy abilities. The effect size in this study was 0.57 with the criteria being moderate or quite influential. It is hoped that teachers in schools can also implement interactive learning, one of which is the use of nearpod media